PENGEMBANGAN BAHAN BELAJAR KEAKSARAAN BERBASIS CERITA RAKYAT KUTAI KALIMANTAN TIMUR - Tri Widayati, O Dollar Sihombing, Widayanti (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2012)
This instructional material development was intended to develop literacy learning material based on Kutai East Kalimantan folklore and examine the approriateness of the learning material. The research was conducted at Community Learning Center of Puteri Karang Melenu, Kutai Kartanegara District, as from May through October 2011. The development model applied ADDIE (Analysis, Design, Develop, Implement, Evaluate) using purposive sampling technique. T-test result for paired samples showed that there was a significant difference between pre-test score and post-test score of the students after used folklore learning material. Meanwhile, from try-out of learning material quality, it was discovered that the criteria for function aspect was very good and the criteria for material, lay out, and language was good.